Pengelolaan Limbah Kotoran Ternak Sapi Menjadi Biogas Sebagai Sumber Pupuk Organik Rumah Tangga - Mahyus; Firdha Mutmainnah Alsyadilah; Khusnul Hatimah. S; Rosita; Yuyun Oktaviani; Andi Zahirul Haq (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Livestock manure is a quality organic fertilizer that can be absorbed by plant roots. Apart from being an organic fertilizer, livestock manure can be used as a renewable energy source. Where this renewable energy is produced with simple appropriate technology in the form of reactors made in accordance with the conditions of rural areas. To utilize livestock manure, Group 27parm, which is a livestock group with 2 members, has utilized cow dung into biogas. In addition to the energy produced, biogas also produces waste that can be used as organic fertilizer. The problem experienced by the 27parm group in Botolempangan hamlet, Purnakarya village, Tanralili sub-district is not only cow dung waste, but now the waste from the fermentation of livestock manure that comes out of the bioreactor in liquid and solid form. Waste generated from the biogas process has a high economic value when processed into solid and liquid organic fertilizers. The purpose of this service is to help solve the partner's problem by increasing partner knowledge in processing biogas waste into organic fertilizer. To increase partner knowledge, training and direct practice are given in processing biogas waste into organic fertilizer. The results of the implementation of this community service are that partners have knowledge and are able to process biogas waste into organic fertilizer. Keywords: Waste; Cattle Manure; Biogas; Organic Fertilizer Abstrak Kotoran ternak termasuk bahan organik yang berkualitas sebagai pupuk yang mampu diserap oleh akar tanaman. Selain sebagai pupuk organik, kotoran ternak dapat dimanfaatan sebagai sumber energi yang terbarukan. Dimana energi terbarukan ini dihasilkan dengan teknologi tepat guna yang sederhana yang berupa reaktor yang dibuat sesuai dengan kondisi daerah pedasaan. Untuk memanfaatkan kotoran ternak, Kelompok 27parm yang merupakan kelompok ternak beranggotakan 2 orang yang sudah memanfaat kotoran sapi menjadi biogas. Selain energi yang dihasilkan, biogas juga menghasilkan limbah yang dapat dimanfaatkan menjadi pupuk organik. Permasalahan yang dialami oleh Kelompok 27parm di dusun Botolempangan desa Purnakarya kec Tanralili bukan saja limbah kotoran sapi, tapi kini limbah hasil permentasi kotoran ternak yang keluar dari bioreaktor dalam bentuk cair dan padat. Limbah yang dihasilkan dari proses biogas mempunyai nilai ekonomis yang tinggi bila diolah menjadi pupuk organik padat dan cair. Tujuan dari pengabdian ini yaitu membantu menyelesaikan permasalah mitra tersebut dengan meningkatkan pengetahuan mitra dalam mengolah limbah biogas menjadi pupuk organik. Untuk meningkatkan pengetahun mitra diberikan pelatihan dan praktek langsung dalam pengolahan limbah biogas menjadi pupuk organik. Hasil pelaksanaan pengabdian pada masyarakat ini mitra memiliki pengetahuan dan mampu pengolahan limbah biogas menjadi pupuk organik. Kata Kunci: Limbah; Kotoran Ternak Sapi; Biogas; Pupuk Organik